If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 34x + 110 = x + 36 Reorder the terms: 110 + 34x = x + 36 Reorder the terms: 110 + 34x = 36 + x Solving 110 + 34x = 36 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 110 + 34x + -1x = 36 + x + -1x Combine like terms: 34x + -1x = 33x 110 + 33x = 36 + x + -1x Combine like terms: x + -1x = 0 110 + 33x = 36 + 0 110 + 33x = 36 Add '-110' to each side of the equation. 110 + -110 + 33x = 36 + -110 Combine like terms: 110 + -110 = 0 0 + 33x = 36 + -110 33x = 36 + -110 Combine like terms: 36 + -110 = -74 33x = -74 Divide each side by '33'. x = -2.242424242 Simplifying x = -2.242424242
| -9-8n=5n-2(4n+2) | | 4(5x-2)+11x-5= | | 13-x=45 | | x+100=x+36 | | x(2x+7)=114 | | 2x+79+7x=14 | | -9+5+4=x+23 | | 2=14-2z | | 9v-v=16 | | (2X+3)-(7x+5)= | | log(9x+8)=2+log(4x-5) | | 1x+(-21)=-31 | | x+8=x+26 | | 6u+u=7 | | 3-4(u-3)=5-u | | 4x-9y=19fory | | 12=6y-2y | | 5a+3-9a+6= | | 7x+3-4=7x+2-3 | | -9p=-36 | | 3m+-5+2m=7m+-24+5 | | v/2=1.77 | | 4y+9=19 | | (2n-2)=(8n+1) | | -30-x=0 | | 4x+3=11x+17 | | 2(v-6)-(-3+6v)=1-2v-2v | | u=3(4n+34)+7(n+1) | | -15x=-90 | | 2y+35=9y-7 | | n=3+3 | | 2x+42=x+42 |